Proceedings of the 12th International Congress on the Archaeology of the Ancient Near East / Volume 2 Field reports, Islamic archaeology - Marchetti, Nicolò; Cavaliere, Francesca; Cirelli, Enrico; D'Orazio, Claudia; Giacosa, Gabriele; Guidetti, Mattia; Mariani, Eleonora (Proceedings of the 12th International Congress on the Archaeology of the Ancient Near East, 2023)
The two volumes include 142 selected lectures presented at the “12th International Congress on the Archaeology of the Ancient Near East” (ICAANE) at the University of Bologna in April 2021. This congress takes place every other year and is the platform for all archaeologists worldwide to present the current results of their research in and on the Near East. The timeframe extends from the Neolithic through the Bronze and Iron ages down to the Achaemenid, Seleuco-Parthian and up to the Islamic period. The geographical frame spans the area from the eastern Mediterranean to Central Asia, and from the Black Sea to the Arabian peninsula. Researchers coming from 43 countries have summarized their latest discoveries mostly in English: the ICAANE proceedings give a state of the art-insight into current research methods and problems of Near Eastern Archaeology.